Recent Development and Validation of Bisacodyl Analysis Method in Tablet with Absorbance Method and Area under Curves Method in Ultraviolet Spectrophotometry - Harrizul Rivai; Nia Pratama; Ridho Asra (Technological Innovation in Pharmaceutical Research Vol. 3, 2021)
Using ultraviolet spectrophotometry with absorbance method and area under the curve, a precise, reliable, quick, and economical simple method for the analysis of bisacodyl tablets has been developed and validated. Using a 0.1 N hydrochloric acid solvent, this process is carried out at a maximum absorption wavelength of 263.60 nm and a region under the curve of 244.40 - 297.60 nm. Linearity, identification limits, quantification limits, precision, and accuracy are all used to validate the process of analysis. The linearity of the absorbance method under the curve is shown by the regression equation y=0.02156x + 0.09258 (r=0.99963), and the linearity of the wide area method is shown by the regression equation y=0.30618x + 1.17400 (r=0.99787). The absorbance method has detection and quantification limits of 1.411099 and 4.276059, while the region under the curve method has detection and quantification limits of 1.968774 and 5.9659197, respectively. The region under the curve and the accuracy obtained by the absorbance approach also meet the validation criteria of 80-120%. The region under the curve and the precision obtained by the absorbance method met the validated criterion with a yield of RSD ? 2%. The paired sample t test was used to conduct statistical analysis, and the results revealed that the two approaches were not substantially different. Both the absorbance method and the small area method are appropriate methods for bisacodyl analysis, as shown by the curves.